Dearomatizing [4+1] Spiroannulation of Naphthols: Discovery of Thermally Activated Delayed Fluorescent Materials. Issue 7 (21st January 2021) - Liang, Wenbo; Yang, Yudong; Yang, Mufan; Zhang, Min; Li, Chengming; Ran, You; Lan, Jingbo; Bin, Zhengyang; You, Jingsong
Abstract: Disclosed here is a palladium‐catalyzed direct [4+1] spiroannulation of ortho ‐C−H bonds of naphthols with cyclic diaryliodonium salts to construct spirofluorenyl naphthalenones (SFNP) under mild reaction conditions. This spiroannulation directly transforms the hydroxy group into a carbonyl group, and also tolerates reactive functional groups such as the halo groups, which provide an opportunity to rapidly assemble structurally new thermally activated delayed fluorescent (TADF) materials that feature a carbonyl group with an adjacent spirofluorenyl unit as the acceptor. As an illustrated example, the OLED device utilizing the assembled DMAC‐SFNP as the host material exhibits a low turn‐on voltage of 2.5 V and an ultra‐high external quantum efficiency of 32.2 %. This work provides inspiration for structurally new TADF materials, and also displays the potential of C−H activation as a synthetic strategy for the innovation of optoelectronic materials. Abstract : A dearomatizing [4+1] C−H spiroannulation of naphthols with cyclic diaryliodonium salts has been developed to rapidly deliver spirofluorenyl naphthalenones, which unlocks an opportunity to discover structurally new thermally activated delayed fluorescent (TADF) materials.